Introduction: Law and the family at the crossroads of democratisation and transnationalisation - Olivier Struelens; Jean De Munck (Oñati Socio-Legal Series, 2024)
In this introduction, the authors present the ambition that guided the composition of this edition devoted to family law. They first highlight the interest in addressing the intersection between the process of democratisation and the process of transnationalisation of families. These two processes are refracted in family law. They find their origin in the same refusal of a substantial moral definition of the “good family”. However, all normative perspective is not abandoned. A new normative and effective relationship is established between interactions and institutions. The new regulation of the family gives an important place to interactions and their immanent normativity. Legal principles (human rights, procedural standards) give expression to this mutation. Institutions are no longer given before the interaction, but rather constitute instruments for repairing the interactional order. This trend in the evolution of the law is particularly visible in the two cases treated in the issue: homosexual marriage and international child abduction. The close analysis of these two situations, however, suggests the persistence of obstacles to these transformations, due to the persistence of the principle of national sovereignty.